The Internationalization Process of the Firm—A Model of Knowledge Development and Increasing Foreign Market Commitments - Johanson, Jan; Vahlne, Jan-Erik (Journal of International Business Studies, 1977)
On the basis of empirical research, a model of the internationalization process of the firm is developed. The model focuses on the gradual acquisition, integration and use of knowledge about foreign markets and operations, and on the incrementally increasing commitments to foreign markets. In particular, attention is concentrated on the increasing involvement in the individual foreign country.